Bovine CD4<sup(+)> T-cell lines reactive with soluble and membrane antigens of Cowdria ruminantium - Totte, P.; Nyanjui, J.; Bensaid, A.; McKeever, Declan J. (1999)
Cowdria-specific CD4<sup(+)> T-cell lines generated from immunized cattle responded to both soluble and membrane proteins of the agent. The lines produced the Cowdria-inhibitory cytokine IFN-<gamma> in response to soluble antigens fractionated by gel filtration and fast performance liquid chromatography. Activity eluted as a single peak around fraction 15 for all T-cell lines tested. This fraction induced the highest production of IFN-<gamma> by the lines and was shown by SDS-PAGE and silver staining analysis to contain less than 10 different bands ranging from 22 to 32 kDa. It is suggested that given their high sensitivity and specificity, these short-term CD4<sup(+)> T-cell lines will be valuable tools for the identification of Cowdria antigens for incorporation in a subunit vaccine.